Computer Programming Self-Efficacy Levels of Engineering Bachelor Students at Eastern Mediterranean University (EMU) - Hanjani, Golmehr Esmaeilzadeh (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2019)
This study assessed Computer Programming Self-Efficacy (CPSE) Levels of engineering bachelor students at Eastern Mediterranean University (EMU). The research method of this study was quantitative method, using the survey technique furthermore a questionnaire with two sections consisting of demographic information plus a computer programming self-efficacy scale, was distributed among 510 engineering students from five different engineering departments, including Computer Engineering, Electrical & Electronics Engineering, Mechanical Engineering, Industrial Engineering and Civil Engineering departments. According to the results the CPSE level of engineering students at EMU can be measured as an average level also in some computer programming related tasks female have a higher CPSE level than male, on the other hand by comparing 5 engineering departments, it can be said that Computer Engineering and Electrical-Electronics Engineering students have a higher CPSE level than others however Civil Engineering students had the lowest CPSE level. Additionally, there was no noteworthy difference among students according to their grade (class level) but overall the CPSE level of 4th Year students were higher than others. Keywords: Self-Efficacy, Computer Programming Self-Efficacy, Engineering Students.

ÖZ:Bu çalışma, Doğu Akdeniz Üniversitesi’ndeki (DAÜ) Mühendislik lisans öğrencilerinin Bilgisayar Programlama Öz-Yeterlilik (CPSE) Düzeylerini incelemektedir. Çalışma nicel araştırma olarak planlanmış ve tarama metodu kullanılmıştır. Veri toplama aracı demografik bilgiler ve bilgisayar programlama öz yeterlilik ölçeği olmak üzere iki bölümden oluşturulmuştur. Çalışmaya, bilgisayar mühendisliği, elektrik-elektronik mühendisliği, makina mühendisliği endüstri mühendisliği ve inşaat dahil olmak üzere beş farklı mühendislik bölümünden 510 mühendislik öğrencisi katılmıştır. Elde edilen sonuçlara göre, mühendislik öğrencilerinin bilgisayar programlama öz yeterlik seviyelerinin orta düzeyde olduğu belirlenmiştir. Diğer taraftan cinsiyet açısından sonuçlar incelendiğinde, tüm bölümlerde kadınların CPSE düzeyinin erkeklerden daha yüksek olduğu söylenebilir. Ek olarak, Bilgisayar Mühendisliği ve Elektrik-Elektronik Mühendisliği öğrencilerinin CPSE seviyelerinin diğer bölümlerdeki öğrencilerden daha yüksek olduğu, İnşaat Mühendisliği öğrencilerinin de en düşük CPSE seviyesine sahip olduğu ortaya çıkmıştır. Ayrıca, tüm bölümlerde 4. Sınıf öğrencilerinin CPSE düzeyinin diğer sınıflardakilere göre daha yüksek olduğu belirlenmiştir. Anahtar Kelimeler: Öz-Yeterlik, Bilgisayar Programlama Öz-Yeterliği, Mühendislik Öğrencileri.
Master of Science in Information and Communication Technologies in Education. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Education, Dept. of Computer Education and Instructional Technology, 2019. Supervisor: Assoc. Prof. Dr. Ersun İşçioğlu.
Keywords: Education; Higher-Literacy; Education; Higher-Evaluation; Academic Literacy Digital competence; Information Literacy-Computer Literacy-Digital Literacy-University Students; Self-Efficacy; Computer Programming Self-Efficacy; Engineering Students